Lobbies in the Making of American Foreign Policy in the South Caucdsus - M. A. Suchkov (Vestnik MGIMO-Universiteta)
The article analyzes the role of lobbies in decision-making in the U.S. toward the South Caucasus states. It also examines lobbying peculiarities of Armenia, Azerbaijan and Georgia as well as mechanisms of their influence over the Congress and American expert community. The author outlines a number of prime issues each Republic lobbies and how they refract U.S. interests in the region.